Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I came across these two series $$\sum_{n=1}^\infty \frac{(-1)^n}{n^2+(n^2-1)^2}$$ and $$\sum_{n=1}^\infty \frac{(-1)^n(n^2-1)}{n^2+(n^2-1)^2}.$$ Does anyone recognize the sums of these series?

share|improve this question
    
These series seem like natural candidates for the Residue Theorem. –  Ron Gordon Feb 5 '13 at 17:11

2 Answers 2

up vote 4 down vote accepted

They can be evaluated in terms of the digamma function, since: $$ n^2 + (n^2-1)^2 = n^4 - n^2 + 1 = (n^2-\omega)(n^2-\omega^2), $$ with $\omega=\exp(2\pi i/3)$, and: $$\sum_{n=1}^{+\infty}\frac{1}{n^2+\alpha}=\frac{-1+\pi\sqrt{\alpha}\coth(\pi\sqrt{\alpha})}{2\alpha},$$ $$\sum_{n=1}^{+\infty}\frac{(-1)^n}{n^2+\alpha}=\frac{-2+\pi\sqrt{\alpha}\coth(\pi\sqrt{\alpha}/2)-\pi\sqrt{\alpha}\tanh(\pi\sqrt{\alpha}/2)}{2\alpha}.$$

share|improve this answer

Using the Residue Theorem, we can show that, for sufficiently well-behaved functions $f(z)$:

$$\sum_{n=-\infty}^{\infty} (-1)^n f(n) = - \sum_{k=1}^m \mathrm{Res}_{z=z_k} \pi \csc{(\pi z)} f(z)$$

where the $z_k$ are the poles of $f$. I will not show this for now, only that I note that $f(z) = (z^2 + (z^2-1)^2)^{-1}$ is sufficiently well-behaved so that we may use the above formula to evaluate the sum.

To find the $z_k$, we solve $ z^2 + (z^2-1)^2 = z^4-z^2+1 = 0$, or

$$z_{(\pm \pm )} = \pm \exp{\left (\pm i \frac{\pi}{6} \right )}$$

We now evaluate the residues associated with the poles and add them up. The result (after some algebra) is

$$\sum_{k=1}^m \mathrm{Res}_{z=z_k} \pi \csc{(\pi z)} f(z) = \pi \csc{\left ( \frac{\pi}{3} \right )} \Im{\left [\exp{\left (-i \frac{\pi}{6} \right )} \csc{\left (\pi \exp{\left (i \frac{\pi}{6} \right )}\right )}\right ]} $$

The computation boils down to the evaluation of $\csc{\left (\pi \exp{\left (i \frac{\pi}{6} \right )}\right )}$. Again, I will spare the reader for now. The result is

$$S = \sum_{n=-\infty}^{\infty} (-1)^n f(n) = \frac{2 \pi}{\sqrt{3}} \frac{\sqrt{3} \cos{\left ( \sqrt{3} \frac{\pi}{2} \right )} \sinh{\left ( \frac{\pi}{2} \right )}+\sin{\left ( \sqrt{3} \frac{\pi}{2} \right )} \cosh{\left ( \frac{\pi}{2} \right )}}{\cosh{\pi} - \cos{(\sqrt{3} \pi)}}$$

However, this is not what we were asked for; rather, the result we seek is

$$\sum_{n=1}^{\infty} (-1)^n f(n) = \frac{1}{2} (S-1) $$

I verified this with a numerical and analytical result in Mathematica.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.